1981
DOI: 10.1111/j.1469-8986.1981.tb03030.x
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Amplitude in a Money‐Winning Paradigm in Children

Abstract: In the present study the influence on P300 amplitude of monetary payoff values linked to stimuli was investigated. Eight school boys (aged 11-13 yrs) were presented with random seriesof four equally frequent visual numeric stimuli (0, 2. 10. and 50). In the payoff condition (PC) subjects were told that each number would indicate the number of German pennies as a winning. In the no-payoff condition (NPC) subjects only had to attend to the stimuli. The amplitude ofa late positive component (P440-540) of the visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
(4 reference statements)
3
15
0
Order By: Relevance
“…Sensitivity of the P3 amplitude to reward magnitude is consistent with previous reports (Begleiter, Porjesz, Chou, & Aunon, 1983;Homberg, Grunewald, & Grunewald-Zuberbier, 1981;Otten, Gaillard, & Wientjes, 1995;Ramsey & Finn, 1997;Yeung & Sanfey, 2004). However, the precise mechanism underlying this effect is not yet well understood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sensitivity of the P3 amplitude to reward magnitude is consistent with previous reports (Begleiter, Porjesz, Chou, & Aunon, 1983;Homberg, Grunewald, & Grunewald-Zuberbier, 1981;Otten, Gaillard, & Wientjes, 1995;Ramsey & Finn, 1997;Yeung & Sanfey, 2004). However, the precise mechanism underlying this effect is not yet well understood.…”
Section: Discussionsupporting
confidence: 91%
“…Stimuli with high emotional value, informative feedback stimuli, and target stimuli also elicit larger P3s than stimuli that do not have these properties (Johnson, 1988;Picton, 1992;Pritchard, 1981). We therefore expected the P3 to be elicited by monetary feedback manipulation; indeed the P3's involvement in monetary reward, and specifically in marking reward's magnitude, has been previously documented (Begleiter, Porjesz, Chou, & Aunon, 1983;Homberg, Grunewald, & Grunewald-Zuberbier, 1981;Otten, Gaillard, & Wientjes, 1995;Ramsey & Finn, 1997;Yeung & Sanfey, 2004). For example, Ramsey and Finn (1997) used a visual discrimination task where subjects were instructed to respond to target stimuli in a neutral condition (no monetary incentive) vs. an incentive condition (monetary gain of 50 cents for correct responses and loss of 50 cents for incorrect responses).…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, P3 amplitude has been shown to be sensitive to the amount of subjects' intentional engagement towards a stimulus and its demand characteristics (Johnson, 1986). Finally, and most important for the present study, it was shown that P3 amplitude is systematically affected by the individual meaning of a stimulus, i.e., by its emotional arousal and individual valence (Begleiter et al, 1967;Hö mberg et al, 1981;Johnston et al, 1986;Farwell and Donchin, 1991;Naumann et al, 1997;Palomba et al, 1997;Schupp et al, 2000). These studies consistently indicate that P3 and LPC amplitudes are largest in response to those stimuli that subjects rate as emotionally meaningful and arousing.…”
Section: Introductionmentioning
confidence: 64%
“…Performing a task with a high financial reward for performance will engage the attentional system stronger and with longer duration than performing the same task with no overt reward for performance. The P3 amplitude is increased with financial incentives for performance (Begleiter et al, 1983;Hömberg et al, 1981). Conceptually, effort (Kahneman, 1973) and motivation are related.…”
Section: Other Factors Impacting Sustained Attentionmentioning
confidence: 99%